Strategi Adaptasi Rumah Tangga Petani Jeruk pada Masa Pandemi Covid-19 dalam Mengatasi Sosial Ekonomi Keluarga di Desa Pengotan, Kecamatan Bangli, Kabupaten Bangli - BAGIA, I KETUT; SUSRUSA, KETUT BUDI; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.13, No.1, November 2024, 2024)
Orange Farmer Household Adaptation Strategy during the Covid-19 Pandemic in Overcoming Family Socio-Economic in Pengotan Village, Bangli District, Bangli Regency. The Covid-19 pandemic has had an impact on various sectors of human life, one of which has an impact on the socio-economic life of farmers. The impact of the Covid-19 pandemic in the agricultural sector was felt by farmers, especially citrus farmers in Pengotan Village, Bangli District, Bangli Regency. This impact needs to be studied more deeply to find out the adaptation strategies carried out by citrus farming households in Pengotan Village in overcoming the socio-economic conditions of their families. The purpose of this study was to determine the socio-economic conditions of citrus farmer households in Pengotan Village and to determine the adaptation strategies adopted to maintain their survival. This type of research is descriptive qualitative and quantitative with survey methods through questionnaires and in-depth interviews with research respondents. Determination of the sample in this study was carried out with the slovin formula so as to get the results of 40 samples. The analytical method used is descriptive analysis with quantitative and qualitative approaches. The results of this study show the socio-economic conditions of citrus farmers in Pengotan Village, Bangli District, Bangli Regency during the Covid-19 Pandemic including income levels, ownership of wealth and housing, education, health, clothing, food and shelter, social interaction and adaptation strategies used. to improve socioeconomic status. To improve their socio-economic, the farmers carry out adaptation strategies. Based on the research results, farmers are more dominant in carrying out active adaptation strategies, as well as strategic adaptive adaptation strategies.